The patterns of leadership behavior prevailing among principals in basic education schools from the teachers’ point of view (a field study in Lattakia) - مبيض مهند; ميهوب ميس (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of the research is to know the leadership behavior patterns prevalent among managers from the point of view of teachers in basic education schools in the city of Lattakia, as well as to know their differences according to the variables of gender, academic qualification,and years of experience. The sample of the study consisted of (374) male and female teachers distributed over the first and second cycle schools. To achieve these goals, the researcher used the descriptive method of research, and used a measure of leadership styles (prepared by the researcher), which consisted of (33) items. The study showed the following results :Leadership patterns prevailing among managers are high. There are no statistically significant differences in the leadership styles of the research sample according to the variables of gender, academic qualification and years of experience.